An effective "three-in-one" screening assay for testing drug and nanoparticle toxicity in human endothelial cells - Filipova, Marcela; Elhelu, Oumsalama K; De Paoli, Silvia H; Fremuntova, Zuzana; Mosko, Tibor; Cmarko, Dusan; Simak, Jan; Holada, Karel (PloS one, 2018)
Evaluating nanoparticle (NP) toxicity in human cell systems is a fundamental requirement for future NP biomedical applications. In this study, we have designed a screening assay for assessing different types of cell death induced by NPs in human umbilical vein endothelial cell (HUVEC) culture. This assay consists of WST-8, LDH and Hoechst 33342 staining, all performed in one well, which enables an evaluation of cell viability, necrosis and apoptosis, respectively, in the same cell sample. The 96-well format and automated processing of fluorescent images enhances the assay rapidity and reproducibility. After testing the assay functionality with agents that induced different types of cell death, we investigated the endothelial toxicity of superparamagnetic iron oxide nanoparticles (SPIONs, 8 nm), silica nanoparticles (SiNPs, 7-14 nm) and carboxylated multiwall carbon nanotubes (CNTCOOHs, 60 nm). Our results indicated that all the tested NP types induced decreases in cell viability after 24 hours at a concentration of 100 μg/ml. SPIONs caused the lowest toxicity in HUVECs. By contrast, SiNPs induced pronounced necrosis and apoptosis. A time course experiment showed the gradual toxic effect of all the tested NPs. CNTCOOHs inhibited tetrazolium derivatives at 100 μg/ml, causing false negative results from the WST-8 and LDH assay. In summary, our data demonstrate that the presented "three-in-one" screening assay is capable of evaluating NP toxicity effectively and reliably. Due to its simultaneous utilization of two different methods to assess cell viability, this assay is also capable of revealing, if NPs interfere with tetrazolium salts.
Keywords: biotest; Apoptosis; Nanoparticles; endoteliální buňky pupečníkové žíly (lidské); apoptóza; lidé; preklinické hodnocení léčiv; velikost částic; Cell Survival; viabilita buněk; Drug Evaluation, Preclinical; Endothelial Cells; Human Umbilical Vein Endothelial Cells; Biological Assay; endoteliální buňky; nanočástice; Particle Size; Humans